Периоды лёта стрекоз в центральных и западных областях Украины - Горб, С.Н.; Павлюк, Р.С. (Вестник зоологии, 1993)
The data on flight period for 61 species (23 Zygoptera, 38 Anisoptera) obtained from literary sources, collection labels and original field observations: maximal flight duration, 10-days period distribution of species on wing, correlation between appearance and disappearance of species. Conclusions as to phenological flight parameters and population changes for certain dragonfly species.